Barriers, facilitators and potential solutions to implementing Kiddie Schedule for Affective Disorder and Schizophrenia (KSADS) screening tool at Muhimbili National Hospital in Dar es Salaam, Tanzania - Leonida Isdory Ngongi; Christopher Fittipaldi Akiba; Mrema Noel Kilonzo; Anna Agape Minja; Charles Onesphor Komba; Mwajabu Rashidi Mbaga; Anna Celestini Msafiri; Lusajo Joel Kajula; Sylvia Florence Kaaya; Brian Wells Pence; Bradley Neil Gaynes (PLoS ONE, 2025)
Background Attention Deficit Hyperactivity Disorder (ADHD) affects 5% of adolescents globally. ADHD increases the child’s risk for adverse outcomes, including school failure, juvenile delinquency, substance abuse, and increased sexual risk behaviors. ADHD can be diagnosed in children using the Kiddie Schedule for Affective Disorders and Schizophrenia (KSADS). Semi-structured or structured diagnostic interviews, such as the KSADS-Present and Lifetime (PL) version by Kaufman and colleagues, are the gold standard in diagnosing psychiatric disorders like ADHD. Nevertheless, KSADS-PL is not used in routine clinical practice in Tanzania. There is no research exploring barriers and facilitators to use of KSADS-PL in resource limited areas including Tanzania. The study aimed to uncover barriers, facilitators and possible solutions related to psychiatric care providers’ routine use KSADS-PL at the Muhimbili National Hospital (MNH) in Dar-es-Salaam, Tanzania. Methods Between July and October 2019, we conducted semi-structured interviews that focused on providers’ perceptions of facilitators, barriers, and solutions regarding KSADS-PL integration into routine clinical practice, data were analyzed data using a qualitative thematic approach informed by the Consolidated Framework for Implementation Research (CFIR). Results Limited knowledge and lack of training about KSADS-PL represented the most mentioned perceived barrier for providers. Some providers reported inadequacy of both human and material resources, high workload, and limited physical space at the clinic. Facilitators included readiness for KSADS-PL implementation, and providers’ desires for uniform and standardized ways of detecting ADHD. Suggested solutions included involving hospital leaders, support for provider training, increasing staff, making KSADS-PL tools readily available, utilizing an online version of the tool, creating departmental standards, maximizing space at the clinic, and reorganizing clinic flow. Conclusion Findings suggest a need for innovative implementation science solutions such as multifaceted educational strategies focusing on ongoing trainings and supervisions to increase clinical knowledge, reorganizing clinic flow to increase the quality and duration of patient‑provider interaction, as well as role shifting and other planning strategies that may address barriers like understaffing.